A reconfigurable and portable acoustofluidic system based on flexible printed circuit board for the manipulation of microspheres. (9th June 2021) - Mikhaylov, Roman; Martin, Mercedes Stringer; Dumcius, Povilas; Wang, Hanlin; Wu, Fangda; Zhang, Xiaoyan; Akhimien, Victory; Sun, Chao; Clayton, Aled; Fu, Yongqing; Ye, Lin; Dong, Zhiqiang; et al.
Abstract: Acoustofluidic devices based on surface acoustic waves (SAWs) have been widely applied in biomedical research for the manipulation and separation of cells. In this work, we develop an accessible manufacturing process to fabricate an acoustofluidic device consisting of a SAW interdigital transducer (IDT) and a polydimethylsiloxane microchannel. The IDT is manufactured using a flexible printed circuit board pre-patterned with interdigital electrodes that is mechanically coupled with a piezoelectric substrate. A new microchannel moulding technique is realised by 3D printing on glass slides and is demonstrated by constructing the microchannel for the acoustofluidic device. The flexible clamping mechanism, used to construct the device, allows the reconfigurable binding between the IDT and the microchannel. This unique construction makes the acoustofluidic device capable of adjusting the angle between the microchannel and the SAW propagation, without refabrication, via either rotating the IDT or the microchannel. The angle adjustment is demonstrated by setting the polystyrene microsphere aggregation angle to −5°, 0°, 6°, and 15°. Acoustic energy density measurements demonstrate the velocity of microsphere aggregation in the device can be accurately controlled by the input power. The manufacturing process has the advantages of reconfigurability and rapid-prototyping to facilitate preparing acoustofluidic devices for wider applications.